2000
DOI: 10.1111/j.1532-5415.2000.tb02589.x
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Ginkgo for Elderly People with Dementia and Age‐Associated Memory Impairment: New Results of a Randomized Clinical Trial

Abstract: OBJECTIVES: To evaluate the efficacy, the dose-dependence , and the durability of the effect of the ginkgo biloba special extract EGb 761 (ginkgo) in older people with dementia or age-associated memory impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
97
2
2

Year Published

2002
2002
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(102 citation statements)
references
References 29 publications
1
97
2
2
Order By: Relevance
“…51,52 In addition, Curcumin was able to reverse the amyloid-induced neuropathology, along with its capacity to block amyloid polymerization. 53 Ginkgo biloba another natural product is largely used as a positive memory modulator 54 and it has been reported that shows prevention of age-related spatial memory deficits in a transgenic mouse model of AD. 55 Also, certain ingredients of green tea modulate APP cleavage sufficiently to reduce the Ab levels and amyloid plaques in AD mouse models.…”
Section: Discussionmentioning
confidence: 99%
“…51,52 In addition, Curcumin was able to reverse the amyloid-induced neuropathology, along with its capacity to block amyloid polymerization. 53 Ginkgo biloba another natural product is largely used as a positive memory modulator 54 and it has been reported that shows prevention of age-related spatial memory deficits in a transgenic mouse model of AD. 55 Also, certain ingredients of green tea modulate APP cleavage sufficiently to reduce the Ab levels and amyloid plaques in AD mouse models.…”
Section: Discussionmentioning
confidence: 99%
“…Recent epidemiological and dietary intervention studies in humans and animals suggest that flavonoids may play a useful role in preventing neurodegeneration, especially age-related cognitive, motoric, and mood decline and protect against oxidative stress as well as cerebral ischemia/ reperfusion injuries. Studies in humans using flavonoidcontaining plant extracts, such as Ginkgo biloba, or pure flavonoid preparations demonstrate positive effects on cognitive function and memory performance in healthy volunteers from all age groups [42,97,213] as well as in patients with age-or Alzheimer' disease-associated dementia [128,146,208]. Watanabe et al [211] reported that G. biloba supplementation in mice had neuromodulatory effects as indicated by a more than three-fold increase of mRNA expression for neuronal tyrosine/threonine phosphatases-1, microtubule-associated tau, prolactin, different calcium, and chloride channels as well as transthyretin.…”
Section: Flavonoids: Neuroprotective Agents In Vivo and In Vitro?mentioning
confidence: 99%
“…Even though the EGb761 is widely used in prescription drugs, the efficacy of EGb761 as a nootropic agent is somewhat controversial. Some clinical trials failed to find any improvement in older people with dementia or age-associated memory impairment (Van Dongen et al, 2000).…”
Section: Introductionmentioning
confidence: 99%